The Academic Leadership of School Administrators under the Bangkok Metropolitan - Wilangsa, Saisamorn; Kanjanaphan, Ratana (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2025)
The purpose of this research is To study the academic leadership of school administrators according to the opinions of teachers in Bangkok and To Compares educational leadership of educational administrators in Bangkok according to their educational level, position and work experience. The research results found that the teachers’ opinions on academic leadership of school administrators, overall and in each section, were at a high level. and Teachers with different levels of education have different opinions on academic leadership of school administrators in Bangkok, overall and in each aspect, that were significantly different at the .05 statistical level. and Teachers with different positions have opinions on the academic leadership of school administrators, overall and in each aspect, and are not different. And teachers with different teaching experiences had opinions on academic leadership of school administrators, overall and in each aspect, that were significantly different at the .05 statistical level.